1985
DOI: 10.1104/pp.77.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ornithine Carbamoyltransferase from Pisum sativum L

Abstract: Some properties of ornithine carbamoyltransferase from chloroplasts isolated from leaves of Pisum sativum L. (cv Marzia) were compared with those of the enzyme partially purified (316-fold) from shoots of seedlings after 3 weeks of cultivation.Both preparations showed a pH optimum at pH 8.3 and had the same affinity to ornithine (K,. = 1.2 millimolar) as well as to carbamoyl phosphate (K,, = 0.2 millimolar). The approximate molecular weight determined by gel sieving was 77,600.A desalted ammonium sulfate preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 9 publications
6
16
0
Order By: Relevance
“…Hybridization with single-stranded RNA probes of opposite polarity to the ROCT frame, produced by in vitro transcription from plasmid pEH10, revealed three transcripts of the size as those detected with the doublestranded probe, while a probe with the same polarity as the ROCT frame did not produce any signal. All (12,16,22) suggested that plant OCTs are present in several subcellular compartments, one of which, the chloroplast, is the most likely cellular target of phaseolotoxin (53,85). Accordingly, we constructed plasmid pEH60 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hybridization with single-stranded RNA probes of opposite polarity to the ROCT frame, produced by in vitro transcription from plasmid pEH10, revealed three transcripts of the size as those detected with the doublestranded probe, while a probe with the same polarity as the ROCT frame did not produce any signal. All (12,16,22) suggested that plant OCTs are present in several subcellular compartments, one of which, the chloroplast, is the most likely cellular target of phaseolotoxin (53,85). Accordingly, we constructed plasmid pEH60 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note, however, that nontrimeric structures have been reported for other plant OTCs. For example, deRuiter and Kolloffel (10) concluded that partially purified pea OTC was a dimer (Mr = 77,600). Recently, Acaster et al (1) reported that the mean Mr value for OTCs from several plant species was 158,000 and the same value was obtained for the carrot enzyme (2), suggesting that the enzyme was most likely a tetramer.…”
Section: Palo-sepharose 65 Affinity Purification Of Plant Otcmentioning
confidence: 99%
“…35,000) contaminating band on SDS-PAGE gels, and it seems likely that the lower mol wt band in their preparation is the proteolytic degradation product. Pea OTC has also been purified by two other groups (10,20), but size estimates for the OTC monomer were not given.…”
Section: Palo-sepharose 65 Affinity Purification Of Plant Otcmentioning
confidence: 99%
“…phaseolicola, Thr*" is replaced by methionine and glycine respectively [42,43]. Both of these plant OTCases exhibit elevated K m values for CP and reduced affinities for the bisubstrate analogue inhibitor, PALO, relative to other OTCases [44,45]. The relatively weak binding of CP to plant OTCases, relative to ATCases, may be important for partitioning CP between de no o pyrimidine and arginine biosynthesis, as a single glutamine-dependent CP synthetase provides the CP intermediate to both pathways [42].…”
Section: Substrate Recognitionmentioning
confidence: 99%